Strategi Pengembangan Lembaga Pendidikan Islam di Daerah Minoritas Muslim dan Kawasan Elite - Bustanul Arifin (FALASIFA : Jurnal Studi Keislaman, 2019)
Educational institutions are very absolute existence today for the smooth process of education, especially in Indonesia. Moreover, educational institutions are associated with the concept of Islam, Islamic educational institutions are a forum where education within the scope of Islam carries out its duties for the achievement of the ideals of the Muslim Ummah. Families, mosques, Islamic boarding schools and madrassas are Islamic educational institutions that are absolutely necessary in a country in general or in a city in particular, because these institutions are like money-making machines that will produce something very valuable, as well as resource printers. qualified and steady human in Islamic aqeedah.Islam requires its people to convey the teachings of Islam to all human masters without exception, but that does not mean also justifies any means, such as coercion and violence. Islam is a religion that rahmatan lil naturalin, so the way to convey it must use a friendly way and its presence can be a blessing for all mankind regardless of differences in religion, creed, race, ethnicity and nation. Islamic educational institutions are one of the Islamic propaganda media, so the development of Islamic educational institutions in an area is an indicator of the development of Islam in the region. Indonesia is a country with a majority Muslim population, but its spread is only concentrated in the western part of Indonesia, while the eastern part of Indonesia is a region that is very minimal almost untouched by Islamic teachings, Islamic educational institutions. The purpose of preparing this paper is to find out the concept of Islamic educational institutions and its development strategy in Muslim minority and elite regions. Educational institutions are very absolute existence today for the smooth process of education, especially in Indonesia. Moreover, educational institutions are associated with the concept of Islam, Islamic educational institutions are a forum where education within the scope of Islam carries out its duties for the achievement of the ideals of the Muslim Ummah. Families, mosques, Islamic boarding schools and madrassas are Islamic educational institutions that are absolutely necessary in a country in general or in a city in particular, because these institutions are like money-making machines that will produce something very valuable, as well as resource printers. qualified and steady human in Islamic aqeedah.Islam requires its people to convey the teachings of Islam to all human masters without exception, but that does not mean also justifies any means, such as coercion and violence. Islam is a religion that rahmatan lil naturalin, so the way to convey it must use a friendly way and its presence can be a blessing for all mankind regardless of differences in religion, creed, race, ethnicity and nation. Islamic educational institutions are one of the Islamic propaganda media, so the development of Islamic educational institutions in an area is an indicator of the development of Islam in the region. Indonesia is a country with a majority Muslim population, but its spread is only concentrated in the western part of Indonesia, while the eastern part of Indonesia is a region that is very minimal almost untouched by Islamic teachings, Islamic educational institutions. The purpose of preparing this paper is to find out the concept of Islamic educational institutions and its development strategy in Muslim minority and elite regions.